A226 INCIDENTAL FINDING OF A LARGE GASTRIC VARIX ASSOCIATED WITH NEONATAL UMBILICAL VEIN CANALIZATION. (4th March 2021) - Tsang, L; Abraldes, J; Wiebe, E; Sandha, G S; van Zanten, S
Abstract: Results: A 41-year old Asian male, who immigrated to Canada many years ago, and who had previously been successfully treated for Helicobacter pylori infection underwent gastroscopy for investigation of dyspepsia. His gastroscopy was normal except for a large subepithelial abnormality that was noted close to the gastroesophageal junction. Routine gastric biopsies from the antrum and body were normal. Subsequent endoscopic ultrasound revealed flow through the anechoic tortuous lesion and confirmed it was a very large isolated gastric varix type 1. Abdominal CT scan revealed chronic occlusion of the portal vein, splenic vein, and the portal confluence with extensive collateralization in the upper abdomen. There was complete cavernous transformation of the portal vein. Of the numerous varices in the upper abdomen, a very large varix drained into the left renal vein and indented into the posterior wall of the fundus of the stomach which accounted for the endoscopic finding. Multiple mesenteric veins were identified that connected to varices adjacent to the inferior aspect of the pancreas and duodenum. Notably, there was no evidence of cirrhosis or chronic pancreatitis. Liver enzymes, albumin, and INR were normal. Further collateral history revealed that he was hospitalized as a neonate for pneumonia with catheterization of the umbilical vein, which is known to be associated with thrombosis of the portal vein. Conclusions: Detection of congenital absence of the portal vein (CAPV) is recognized more often due to advances in diagnostic imaging. Radiologically, the absence of the portal vein in CAPV is distinguished from portal vein thrombosis by the lack of venous collaterals or sequalae of portal hypertension, such as ascites or splenomegaly. A more gradual thrombosis of the portal vein may permit collaterals to develop without acute changes and is not equivalent to portal vein aplasia or agenesis as intrahepatic bile ducts are normal. The gold standard for diagnosis of CAPV is histologic absence of the portal vein in the liver on catheter angiography. CAPV is associated with abnormal embryologic development of the portal vein and frequently presents with complications of portal hypertension or portosystemic encephalopathy or the sequalae of venous shunts, hepatic or cardiac abnormalities found on imaging. Our case is an incidentally discovered absence of the portal venous system due to chronic thrombosis with extensive collateralization and an enlarged gastric varix protruding into the proximal stomach. It is well documented that canalization of the umbilical vein in infancy is associated with portal vein thrombosis, with incidences up to 68%. This case highlights the importance of eliciting a childhood hospitalization history in cases of non-cirrhotic portal hypertension. Funding Agencies: None